A protection strategy for micro grids based on positive sequence impedance - Mirsaeidi, Sohrab (Taylor and Francis, 2016)
In recent years, the concept of micro-grid has appeared as an appropriate way for the integration of Distributed Energy Resources (DERs) in the distribution networks. However, micro-grids have encountered a number of challenges from control and protection aspects. One of the main issues relevant to the protection of micro-grids is to develop a suitable protection technique which is effective in both grid-connected and stand-alone operation modes. This article presents a new micro-grid protection strategy based on positive-sequence impedance using Pha-sor Measurement Units (PMUs) and a designed Microprocessor-Based Relay (MBR) along with a narrowband communication system (only to exchange digital information, not electrical power). The main attribution of the proposed scheme is that it has the ability to protect micro-grids containing either radial or looped feeders; additionally, the capabilities of automatic updating of pick-up threshold value and single-phase tripping have been considered in the designed MBR. Finally, in order to verify the effectiveness of the suggested scheme and the designed MBR, several simulations have been undertaken by using DIgSILENT Power-Factory and Matlab software packages.